Implementation and Development of Emergency Department Pharmacist-Driven Patient-Care Transitional Model: A Discussion of Our Experiences and Processes - Arinze Nkemdirim Okere (University of Minnesota Libraries Publishing, 2018)
Frequent preventable emergency department (ED) visits is an area of great concern among healthcare administrators. Although pharmacist interventions have been shown to reduce re-hospitalizations, studies demonstrating reduction in ED utilizations among the elderly are limited. Additionally, factors influencing readmissions in the ED are multifactorial. Hence, some healthcare systems struggle to reduce readmissions using pharmacy services. This has been a major issue facing care provided to the elderly in the ED. As healthcare care systems develops and implement a collaborative pharmacist and physician/mid-level provider comprehensive transitional model of care in the ED, the quality of care provided to the elderly will be enhanced which will ultimately translate to reduced inappropriate ED visit and re-hospitalization with corresponding reduction in financial burden placed on both the patient, caregiver and the society. Therefore, the objective of this article is to discuss our process with implementing pharmacist-providers transitional model in the ED. The intent is to elucidate some pharmacist-intervention principles and a pharmacist-driven, patient-care transitional model that would provide direction for other healthcare systems to improve ED visits within their locality.   Type: Idea Paper